Embodied Social Proxy: Mediating Interpersonal Connection in Hub-and-Satellite Teams - Venolia, Gina; Tang, John; Cervantes, Ruy; Bly, Sara; Robertson, George; Lee, Bongshin; Inkpen, Kori (Proceedings of CHI 2010, 2010)
Current business conditions have given rise to distributed teams that are mostly collocated except for one remote member. These “hub-and-satellite” teams face the challenge of the satellite colleague being out-of-sight and out-of-mind. We developed a telepresence device, called an Embodied Social Proxy (ESP), which represents the satellite coworker 24x7. Beyond using ESPs in our own group, we deployed an ESP in four product teams within our company for six weeks. We studied how ESP was used through ethnographic observations, surveys, and usage log data. ESP not only increased the satellite worker’s ability to fully participate in meetings, it also increased the hub’s attention and affinity towards the satellite. The continuous physical presence of ESP in each team improved the interpersonal social connections between hub and satellite colleagues.